New Educational Equipments for Networking Study by Physical Visualizations and Physical Direct Manipurations - Yoshihara, Kazuaki; Watanabe, Kenzi; Iguchi, Nobukazu (Proceedings / International Conference on Advanced Information Networking and Applications, 2016)
Studying networking technologies has become one of the most important subjects in the field of Technology of junior high schools and Information Study of senior high schools in Japan. To study these subjects, studying with practically and experimentally is strongly recommended by MEXT (Ministry of Education, Culture, Sports, Science and Technologies in Japan). However, there is little equipment for these studies. We have been developing new educational equipment for experimental studying of networking technologies based on concept of physical visualizations and physical direct manipulations. The equipment can visualize physically how network works using LED. Also the equipment provide physical direct manipulation using dials and buttons.